PENERAPAN HUKUM PIDANA ISLAM DALAM MENANGGULANGI DAMPAK NEGATIF JUDI ONLINE PADA MASYARAKAT - Musli, ode; Tubaka, Abdul Manaf; Haryanti, Tuti; La Jamaa (TAHKIM, 2025)
This research examines the application of Islamic criminal law in addressing the negative impacts of online gambling on society, both socially and economically. The main objective of this study is to analyze the effectiveness of applying Islamic criminal law in dealing with the negative impacts caused by online gambling through a normative juridical approach. The method used is normative juridical, examining laws and regulations, fatwas, and the principles of Islamic criminal law relevant to online gambling issues. The findings show that although Islamic criminal law is firm on gambling, its application within Indonesia's positive law has not been fully effective in mitigating the negative impacts of online gambling. In conclusion, the application of Islamic criminal law can be an alternative solution to address the negative impacts of online gambling, but it requires harmonization with the prevailing positive law in Indonesia. Additionally, preventive efforts from the government and society are necessary to prevent the spread of online gambling. Keywords: Islamic criminal law, online gambling, social impact, preventive efforts